Treino de potência em adultos de meia-idade, idosos saudáveis e com limitação na mobilidade: adaptações no sistema neuromuscular e seus efeitos sobre o desempenho funcional - Schaun, Gustavo Zaccaria (2021)
This doctoral thesis aimed to evaluate and compare the neuromuscular, morphological and functional adaptations of a high-velocity resistance training program in middle-aged adults (40-55 years), older adults (60+ years) and mobility-limited older adults (Short Physical Performance Battery; SPPB ≤ 9). For this, 43 participants were recruited (19 adults, 18 older adults, and 8 mobility-limited older adults) and tested for maximal isometric strength and neuromuscular activity, as well as maximal dynamic strength (1RM) and power, force, and velocity at a wide range of submaximal intensities (30- 90%1RM). Muscle thickness and quality were also measured, as well as functional performance, assessed through the SPPB test, maximal and usual gait speed, 30 s sitto-stand, stair climb, timed up-and-go, and the 6-min walk test. Participants underwent 12 weeks of high-velocity resistance training with a frequency of two sessions per week and repeated the tests at the end of the intervention. Specifically, two studies make up the volume of this thesis. The first corresponds to a narrative review article and analyzes the effects of high-velocity resistance training in older adults with and without mobility limitations, in addition to presenting an overview of the main effects of neuromuscular aging on the functional capacity of these individuals. The second article presents the results of the intervention on the neuromuscular, morphological and functional capacity outcomes investigated, which are accompanied by an extensive set of supplementary materials. Overall, our results demonstrate that a short-term high-velocity resistance training intervention leads to an important functional reserve in middle-aged individuals, while it also mitigates physiological and functional impairments already present in older adults with and without mobility limitation.